Effects of Dried Bovine Amniotic Membrane as Prosthetics of Abdominal Fascial Defect Closure Observed by the Expression of Platelet-Derived Growth Factor in Rattus norvegicus Wistar Strain - Nurul Huda Didiek Putra, -
Abstract Abdominal wall defect is a condition often occurring after surgery or trauma. Amniotic membrane is believed to contain growth factors including epidermal growth factors (EGF), platelet-derived growth factor (PDGF), and transforming growth factor-beta. This study aimed to analyze differences in PDGF levels in abdominal fascia defects in which closure was performed with and without dried bovine amniotic membrane. This was an experimental research design on experimental animals of 32 Rattus norvegicus Wistar strain divided into two groups, control and treatment. PDGF evaluation was measured using the immunohistochemical examination. Measurements were made subjectively by two anatomical pathologists separately with a scoring system. Evaluation of PDGF expression examination was assessed by the intensity and percentage of positive cells. There was no significant difference in PDGF intensity (p = 0.763) between the treatment and control groups. Meanwhile, the PDGF extension found a significant difference (p = 0.005). PDGF expression was obtained by multiplying the intensity score by extension, and the results obtained were significantly different (p = 0.008). PDGF expression in the treatment group was higher than in the control group. Closing the abdominal fascial defect using dried bovine amniotic membranes can increase PDGF expression.